2014
DOI: 10.4028/www.scientific.net/amm.625.196
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Composition of the Crude Oils on the Wax Crystallization

Abstract: One of the major problems in petroleum industry is wax precipitation and deposition. The component’s compositional and structural analysis of the crude oils is key factors to be studied to mitigate wax formation and precipitation tendency for the betterment of the crude oil flowability. In this work, the compositions and structures of two Malaysian and Sudanese crude oil samples were determined to investigate their effects on wax precipitation. The GC/MS was used to analyze hydrocarbon components. For this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Wax prevention is of paramount importance in the petroleum industry, especially during production in gas-lift wells. There are several well-known methods [12][13][14][15][16][17][18] used to handle wax formation problems such as mechanical-removal methods, chemical inhibitors, thermal techniques, chemical solvents, and other methods. Although there are several methods that have been applied to handle the wax formation problem in recent decades, questions concerning their economic viability as well as their effectiveness remain relevant.…”
Section: A Methods Of Hot Apg Injection To Prevent Wax Deposit Formation In Gas-lift Wellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wax prevention is of paramount importance in the petroleum industry, especially during production in gas-lift wells. There are several well-known methods [12][13][14][15][16][17][18] used to handle wax formation problems such as mechanical-removal methods, chemical inhibitors, thermal techniques, chemical solvents, and other methods. Although there are several methods that have been applied to handle the wax formation problem in recent decades, questions concerning their economic viability as well as their effectiveness remain relevant.…”
Section: A Methods Of Hot Apg Injection To Prevent Wax Deposit Formation In Gas-lift Wellsmentioning
confidence: 99%
“…Well-known methods to prevent and mitigate wax deposits in downhole equipment during the operation of gas-lift wells are mechanical, thermal, and chemical methods [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Although, there are several methods that have been applied to handle the wax formation problem in recent decades, questions concerning their economic viability as well as their effectiveness remain relevant. Moreover, the effect of the component composition of fluids on the wax formation process has been studied by a number of researchers [49][50][51][52]. The authors showed that the light-end hydrocarbon components (С 1 -С 4 ) and the remaining components (heavy fractions) play completely different roles in wax crystallization and as a result, they have a great impact on the WAT.…”
Section: A Comprehensive Solution To Preventing the Formation Of Wax ...mentioning
confidence: 99%
“…The continuous wax build-up obstructs oil flow and leads to marginal oil recovery and the shutdown of the production pipeline (Sharma et al, 2016). On top of that, oil companies lose millions of dollars annually due to the reduced oil production and high cost of wax removal (Hosseinipour et al, 2014). The flow assurance problems also reflect the rising cost of production because extra horsepower and workforce are needed to alleviate the pressure to prevent wax deposition (Elsharkawy et al, 2000).…”
Section: Introductionmentioning
confidence: 99%